Translating the epidemic of fear-based rhetoric in Canadian press: A case study and framework - Desjardins, Renee (University of Ottawa (Canada), 2006)
News, as we know, saturates our lives: from the morning newspaper to televised late-night reports there is no denying the influence and impact media can have on our daily lives. In the context of a post September the 11th world, one of the dominant trends in press media is the use of fear-based rhetoric. This research paper is concerned with how the Canadian press media constructs fear, particularly the fear of disease, and how this fear is further disseminated through translation. As well, it explores some of the dominant discourses concerning translation in the press and in general. The main hypothesis is that translation acts as a space of contagion with the power to disseminate certain emotions that develop in response to current events. Observations include a case study of French and English-Canadian press articles on the avian flu and the discursive strategies used to convey fear of the disease, as well as a potential framework for translators of the press.
Keywords: Journalism.; Language, Rhetoric and Composition.